THE IMPACT OF BRAND REPUTATION AND BRAND IMAGE ON BRAND LOYALTY APPLE (Study on Apple Brand Consumers in Medan City) - Novrianda Wirayudha; Feby Aulia Safrin (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to analyze how the influence of brand reputation and brand image on brand loyalty of apple. The influence between brand reputations and the brand image will be analyzed partially and simultaneously on brand loyalties. The form of research used is quantitative with an associative approach. The population in this study used the Lemeshow formula with a total of 96 respondents as samples. The primary data used in this study was obtained by distributing the questionnaire directly while the secondary data was acquired through a library study. Data analysis methods used are instrumental testing, classical assumption testing, double linear regression analysis and hypothetical testing using SPSS. The results of the research showed that brand reputation and brand image have a significant influence both partially and simultaneously on brand loyalty in Apple consumers in the City of Medan. The determination coefficient test showed that there was a close relationship between the variable with the R value of 0.614. Through the adjusted R square value it was also known that the brand reputation and brand image variables contributed 36.4% to brand loyalty variable while the remaining 63.6% was influenced by other variables outside this study model.